1998
DOI: 10.1038/bjc.1998.223
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal imbalances in primary and metastatic pancreatic carcinoma as detected by interphase cytogenetics: basic findings and clinical aspects

Abstract: Summary To date, cytogenetic studies on pancreatic carcinoma are rare, and little is known about the frequency of cytogenetic aberrations in primary carcinomas compared with metastatic tumour cells. We therefore evaluated the frequency of chromosomal aberrations in 12 primary pancreatic carcinomas and in effusion specimens from 25 patients with pancreatic cancer by using interphase fluorescence in situ hybridization (FISH) and a panel of four centromeric probes. Hyperdiploidy and chromosomal imbalances, predom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 29 publications
3
25
0
Order By: Relevance
“…In contrast, an immunohistochemical study failed to detect overexpression of c-MYC in 20 pancreatic cancers (13). Recently, amplification of the c-MYC oncogene was identified by FISH in 2 of 10 metastatic pancreatic effusion cells (14) and in 4 of 7 human xenografted pancreatic tumors (5). However, all studies pertaining to c-MYC in pancreatic cancer are based on small tumor numbers and appear therefore of limited validity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, an immunohistochemical study failed to detect overexpression of c-MYC in 20 pancreatic cancers (13). Recently, amplification of the c-MYC oncogene was identified by FISH in 2 of 10 metastatic pancreatic effusion cells (14) and in 4 of 7 human xenografted pancreatic tumors (5). However, all studies pertaining to c-MYC in pancreatic cancer are based on small tumor numbers and appear therefore of limited validity.…”
Section: Discussionmentioning
confidence: 99%
“…To date, little is known about genomic and proteomic changes affecting c-MYC in pancreatic cancer. The available data are controversial and show a varying incidence of c-MYC deregulation in the small number of pancreatic cancers analyzed (5,(12)(13)(14). Therefore, further and more detailed investigations to assess the biological significance and prognostic value of c-MYC activation in pancreatic carcinogenesis are demanded.…”
mentioning
confidence: 99%
“…Cytogenetic analyses of primary and metastatic pancreatic carcinomas have shown that chromosome abnormalities occur at higher frequencies in metastatic tumors than in primary tumors (Zojer et al, 1998). Alterations in the numbers and structures of chromosomes reflect defective mitosis, including unequal distribution of chromosomes to daughter cells.…”
Section: Shono Et Almentioning
confidence: 99%
“…In fact, pancreatic cancer is frequently characterized by numerical and structural aberrations in chromosomes, a hallmark of genetic instability (Griffin et al, 1995;Hahn et al, 1995). Cytogenetic analyses of primary and metastatic pancreatic carcinomas have shown that chromosomal abnormalities occur at higher frequencies in metastatic tumors than in primary tumors (Zojer et al, 1998). Furthermore, pancreatic carcinomas xenografted in nude mice acquire a higher degree of genetic aberration during tumor dissemination (Reyes et al, 1996).…”
mentioning
confidence: 99%
“…An assortment of genetic procedures have been attempted to investigate pancreatic cancer, including family history studies, 1 conventional cytogenetic techniques, 10 interphase FISH, [11][12][13] comparative genomic hybridization, 14 RNA expression analyses, 15, 16 and evaluation of sequence variations. 17 These studies implicate a variety of point mutations and chromosomal anomalies in most, if not all, patients with pancreatic cancer.…”
Section: Fluorescence In Situ Hybridization To Visualize Genetic Abnomentioning
confidence: 99%